Comparison of the psychological significance of stress and learning among university students from Mexico and Costa Rica (Dissertare, 2020)
Stress is one of the most serious problems of the 21st century, classified as a complex public health problem with a multidisciplinary solution. It is produced by interpreting a stimulus as demand and perceiving that it exceeds the available resources to face it. In the educational field, “academic stress” occurs, when school activities are perceived as difficult demands to cope with. For this reason, it is relevant to investigate the meaning that students attribute to learning and stress, as well as the way in which they relate them. The objective of this research is to compare the psychological meaning attributed to such concepts by two samples of university students from Mexico and Costa Rica, as well as to contrast the way in which both groups relate these elements. The sample included 110 university students from the area of ​​Social Sciences, 55 from Costa Rica and the same number from Mexico. The Natural Semantic Networks technique was used to collect the data, through the JSARS platform. The results show that both Mexican university students and Costa Ricans associate stress with elements of the teaching-learning process, such as “homework”, “school”, “exams” and “studying”, perceiving them as stressors. However, there are differences in the perception of the two concepts analyzed between the samples studied, in aspects such as: semantic richness; semantic density; and semantic weight of sources of stress associated with learning. It is concluded that there are cultural differences in the meaning of "stress and" learning "between the two samples, but in both, the latter has a stressful conceptual connotation.
Keywords: stress; academic stress; stress in university students; natural semantic networks